Geographical origin traceability and species identification of three scallops (Patinopecten yessoensis, Chlamys farreri, and Argopecten irradians) using stable isotope analysis. (30th November 2019) - Zhang, Xufeng; Cheng, Jinping; Han, Deming; Zhao, Xinda; Chen, Xiaojia; Liu, Yu
Highlights: 575 training samples and 150 testing samples from seven sites in China were collected. Stable isotope analysis was first used to identify the origin and species of scallop. δ 13 C and δ 15 N of scallops differed significantly between origins, seasons and species. 92% of correct classification was obtained by LDA for origin prediction. 98.3% accuracy was obtained by LDA for species prediction. Abstract: Traceability and authenticity is crucial to the food safety of scallop. The present study investigated the possibility of using stable isotope analysis to identify the origins and species of scallops ( Patinopecten yessoensis, Chlamys farreri, and Argopecten irradians ) in the coastal areas of China. The δ 13 C and δ 15 N values of a total of 575 samples from seven sites around China were determined and additional 150 samples were tested by fisher linear discrimination analysis (LDA) to estimate the accuracy of origin identification and species prediction. The results show that the stable C and N isotope composition differed significantly depending on the origin, season and species of scallops. Meanwhile, the LDA shows that 92% of the samples were correctly classified for origin prediction, and an accuracy of 98.3% was obtained for species prediction. This study reveals that stable isotope ratio is an effective technique to trace the geographical origin and identify the species of scallops.